2019
DOI: 10.1523/jneurosci.2121-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

Conditional BDNF delivery from astrocytes rescues memory deficits, spine density and synaptic properties in the 5xFAD mouse model of Alzheimer disease

Abstract: It has been well documented that neurotrophins, including brain-derived neurotrophic factor (BDNF), are severely affected in Alzheimer's disease (AD), but their administration faces a myriad of technical challenges. Here we took advantage of the early astrogliosis observed in an amyloid mouse model of AD (5xFAD) and used it as an internal sensor to administer BDNF conditionally and locally. We first demonstrate the relevance of BDNF release from astrocytes by evaluating the effects of coculturing WT neurons an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
109
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(120 citation statements)
references
References 81 publications
8
109
1
2
Order By: Relevance
“…Evidence for the involvement of astrocytes in BDNF-mediated cognitive outcomes is numerous. For example, astrocytes expressing a truncated form of TrkB T1 respond to application of BNDF by releasing Ca 2+ from intracellular space [ 82 ], astrocytes respond to increased BDNF by expression of TrkB receptors [ 83 ], astrocytes themselves produce the BDNF protein as it was shown in our study and in previous works [ 84 , 85 ], and BDNF released from astrocytes is crucial for dendrite spine density and morphology [ 86 ]. Importantly, BDNF has been shown to regulate astrocytic morphology through TrkB-T1 receptors located specifically in GFAP+ astrocytes [ 26 , 87 ].…”
Section: Discussionmentioning
confidence: 70%
“…Evidence for the involvement of astrocytes in BDNF-mediated cognitive outcomes is numerous. For example, astrocytes expressing a truncated form of TrkB T1 respond to application of BNDF by releasing Ca 2+ from intracellular space [ 82 ], astrocytes respond to increased BDNF by expression of TrkB receptors [ 83 ], astrocytes themselves produce the BDNF protein as it was shown in our study and in previous works [ 84 , 85 ], and BDNF released from astrocytes is crucial for dendrite spine density and morphology [ 86 ]. Importantly, BDNF has been shown to regulate astrocytic morphology through TrkB-T1 receptors located specifically in GFAP+ astrocytes [ 26 , 87 ].…”
Section: Discussionmentioning
confidence: 70%
“…Because reduced levels of protein markers of synaptic health (e.g. PSD-95) are generally not observed in 5xFAD until they are at least 6-months of age [34,63,107,108], future experiments will be required to determine whether TLQP-21mediated rescue of amyloid and microglial phenotypes in male 5xFAD mice at 5 months of age is associated with memory improvement and reduced synaptic damage as the TLQP-21-treated mice age. Importantly, we find that human TLQP-21 activates human microglia with similar outcomes to the activation of murine microglia by mouse TLQP-21, confirming the potential relevance of the mechanisms and pathways that we described for human disease.…”
Section: Discussionmentioning
confidence: 99%
“…pGFAP-BDNF mice display worse phenotype and increased neuronal death in the lithium-pilocarpine model of TLE First, since it has been widely demonstrated that BDNF is expressed and released by astrocytes [20][21][22][23] , we aimed to study the role of the neurotrophin produced by astrocytes in a TLE model by using wild-type (WT) mice and the pGFAP-BDNF transgenic mice as a gain-of-BDNFfunction approach. In these mice, BDNF is overexpressed only under pathological conditions 20,21 . To do so, first we subjected pGFAP-BDNF mice and their WT controls to the lithium-pilocarpine model (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that in vitro and in vivo astrocytes produce and release BDNF [20][21][22][23] . To functionally explore the influence of astrocytic BDNF over the neuronal population response in an epileptic context we used a loss-and a gain-of-BDNF-function approach Data were analyzed by two-way ANOVA followed by Bonferroni's test.…”
Section: Bdnf From Astrocytes Regulates the Hyperactivation Of Neuronmentioning
confidence: 99%